Stem-cell gene therapy for the Wiskott-Aldrich Syndrome - Boztug, Kaan; Schmidt, Manfred; Schwarzer, Adrian; Banerjee, Pinaki P.; Díez, Inés Avedillo; Dewey, Ricardo A.; Böhm, Marie; Nowrouzi, Ali; Ball, Claudia R.; Glimm, Hanno; Naundorf, Sonja; Kühlcke, Klaus; et al. (The New England journal of medicine, 2010)
The Wiskott-Aldrich syndrome (WAS) is a complex primary immunodeficiency disorder that is characterized by recurrent infections, thrombocytopenia, eczema, and autoimmunity1,2 and caused by mutations in WAS.3 Its gene product, WAS protein (WASP), is a key regulator of actin polymerization in hematopoietic cells, with domains involved in signaling, cell locomotion, and immunologic-synapse formation.4 The complex biologic features of this disease result from multiple dysfunctions in different subgroups of leukocytes, including defective function of T and B cells, disturbed formation of the NK-cell immunologic synapse, and impaired migratory responses in all leukocyte subgroups.4,5 Severe WAS leads to an early . . .